In a zebrafish biomedical model of human Allan-Herndon-Dudley syndrome impaired MTH signaling leads to decreased neural cell diversity - Silva, Nádia; Campinho, Marco António (Frontiers in Endocrinology, 2023)
Maternally derived thyroid hormone (T3) is a fundamental factor for vertebrate neurodevelopment. In humans, mutations on the thyroid hormones (TH) exclusive transporter monocarboxylic acid transporter 8 (MCT8) lead to the Allan-Herndon-Dudley syndrome (AHDS). Patients with AHDS present severe underdevelopment of the central nervous system, with profound cognitive and locomotor consequences. Functional impairment of zebrafish T3 exclusive membrane transporter Mct8 phenocopies many symptoms observed in patients with AHDS, thus providing an outstanding animal model to study this human condition. In addition, it was previously shown in the zebrafish mct8 KD model that maternal T3 (MTH) acts as an integrator of different key developmental pathways during zebrafish development. Using a zebrafish Mct8 knockdown model, with consequent inhibition of maternal thyroid hormones (MTH) uptake to the target cells, we analyzed genes modulated by MTH by qPCR in a temporal series from the start of segmentation through hatching. Survival (Tunnel) and proliferation (PH3) of neural progenitor cells (dla, her2) were determined, and the cellular distribution of neural MTH-target genes in the spinal cord during development was characterized. In addition, in-vivo live imaging was performed to access NOTCH overexpression action on cell division in this AHDS model. We determined the developmental time window when MTH is required for appropriate CNS development in the zebrafish; MTH is not involved in neuroectoderm specification but is fundamental in the early stages of neurogenesis by promoting the maintenance of specific neural progenitor populations. MTH signaling is required for developing different neural cell types and maintaining spinal cord cytoarchitecture, and modulation of NOTCH signaling in a non-autonomous cell manner is involved in this process. The findings show that MTH allows the enrichment of neural progenitor pools, regulating the cell diversity output observed by the end of embryogenesis and that Mct8 impairment restricts CNS development. This work contributes to the understanding of the cellular mechanisms underlying human AHDS.